PREFERENSI KONSUMEN TELUR PUYUH DI KOTA KENDARI - Sani Wanti; Sitti Aida Adha Taridala; Takdir Saili; Budiyanto Budiyanto (Universitas Halu Oleo, 2017)
The preference of quail egg’s consumer could be determined by measuring the consumer choice. This preference could illustrate the attribute of quail egg that could be produced by producer and accepted by consumer. The aims of this study were to analyze the attitude and behavior of the customer in case of buying quail egg, analyze the level of self interest and satisfaction of the customer to the quail egg attribute, and analyze the customer preference on a variety of the quail egg attributes. Data collected in Kendari, South East Sulawesi and were analyzed using Fishbein Multiattribute Attitude analysis, IPA analysis (Importance Performance Analysis), and Conjoint Analysis. The result of Fishbein Multiattribute Attitude Analysis indicated that the 61,91% consumers were fond of quail egg. In average, the acceptabiity of the customer to the quail egg was ‘quite good’ and the behavior of the customer was consistent but they to re-buy the quail egg. While the result of IPA analysis (Importance Performance Analysis) showed that the most important and the most satisfine attribute of quail egg for customer was colourful attribute. The result of Conjoint Analysis revealed that the preference of the quail egg customer in Kendari City was the quail egg with low price, seasonal availability, less than 10 gram in weight, colourful and unpacking. Keywords: quail egg; Fishbein; IPA; Conjoint analysis